Successful Treatment of a Single Giant Renal Cyst in a Newborn with Drainage and Sclerotherapy - Koenig, Adriana; Ménétrey, Anika; Jhala, Tobias; Uerlings, Vincent; Szavay, Philipp O. (European Journal of Pediatric Surgery Reports, 2022)
Simple renal cysts are a scarce entity in pediatric patients and their etiology is unknown in most cases. Usually, they are monitored with ultrasound and regular follow-up of renal function. Surgical treatment is rarely indicated. We report the case of a newborn with a single giant renal cyst that could be treated successfully with drainage and sclerotherapy. Single giant renal cysts require careful investigation and monitoring. In cysts without communication to the pelvico-caliceal system, sclerotherapy by instillation of doxycycline is a therapeutic option.
Keywords: renal cyst; sclerotherapy; single giant renal cyst